Листовійки (Lepidoptera, Tortricidae) Графського парку та агробіостанції Ніжинського державного університету імені Миколи Гоголя (Чернігівська область, Україна) - Kavurka, V. V. (public organization "Ukrainian Entomological Society", I.I. Schmalhausen Institute of Zoology of National Academy of Sciences of Ukraine, Institute of Plant Protection of National Academy of Agrarian Sciences of Ukraine, 2018)
An annotated list of tortricid moths (Lepidoptera, Tortricidae) of the Grafsky Park and the agrobiostation of the Nizhyn Mykola Gogol State University is given for the first time. In total, from 1987 to 2018, 95 species of 13 tribes were identified in the studied area: Tortricini – 6 species, Cochylini – 12 species, Cnephasiini – 7 species, Archipini – 12 species, Sparganothini – 1 species, Endotheniini – 4 species, Bactrini – 2 species, Olethreutini – 12 species, Lobesiini – 1 species, Enarmoniini – 6 species, Eucosmini – 22 species and Grapholitini – 9 species. It is about 40% of the species diversity of tortricid moths of Chernihiv region known now, and about 17% of the fauna of Ukraine. The distribution and biology of the recorded species are analized. Herein 54 species of tortricid moths are recorded for Chernihiv region for the first time, 34 species (Tortrix viridana, Aleimma loeflingiana, Acleris holmiana, A. forsskaleana, Eupoecilia ambiguella, Archips podana, A. crataegana, A. xylosteana, Choristoneura diversana, Argyrotaenia ljungiana, Ptycholoma lecheana, Pandemis corylana, P. cerasana, P. heparana, Syndemis musculana, Adoxophyes orana, Apotomis betuletana, Orthotaenia undulana, Hedya salicella, H. nubiferana, H. pruniana, H. ochroleucana, Ancylis achatana, A. mitterbacheriana, Spilonota ocellana, Gibberifera simplana, Epinotia nisella, Notocelia uddmanniana, Cydia pomonella, C. pyrivora, C. fagiglandana, C. splendana, C. amplana, Grapholita funebrana) are known as pests of deciduous trees and 4 species (Piniphila bifasciana, Gravitarmata margarotana, Rhyacionia buoliana, Cydia strobilella) are known as pests of coniferous trees.